MAGNETIC HILLS AND OPTICAL ILLUSION IN KURDISTAN REGION - Parekhan M. Jaff; Kharman A. Faraj (European Scientific Journal, ESJ, 2013)
“Anti-Gravity Hills", or “Magnetic Hills”, are natural places where apparently defying the law of gravity. In some places in Kurdistan region these magnetic hills exist. This type of hills appears to go uphill is really going downhill. The purpose of the present work was to register an unknown magnetic hill, and a water channel of abnormal apparent direction of flow! And to study what types of physical properties are behind these, we investigated that optical illusion, and a false horizon line are behind.